2006
DOI: 10.1163/156854106779799259
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium oxysporum endophytes induced systemic resistance against Radopholus similis on banana

Abstract: Four mutualistic endophytic fungal isolates were investigated for their ability to induce systemic resistance in banana toward the burrowing nematode, Radopholus similis in glasshouse experiments. Two isolates of Fusarium oxysporum and one of F. cf. diversisporum isolated from the cortical tissue of banana, and another isolate of F. oxysporum isolated from tomato, were compared. When the root systems of seedling banana plants were pre-inoculated with the four endophytic fungi, R. similis root penetration was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(68 citation statements)
references
References 16 publications
3
57
1
2
Order By: Relevance
“…It can therefore be assumed that the isolates collected in this study either represent generally nonpathogenic strains or that they represent strains pathogenic to plants other than tomato. Nevertheless, inoculation of the FOSC reference strain, Fo162, on various tomato cultivars and other plants, like melon, pepper, Arabidopsis and banana has never resulted in disease development Vu et al 2006;Martinuz et al 2015).…”
Section: Diversity Of Root Endophytesmentioning
confidence: 99%
See 1 more Smart Citation
“…It can therefore be assumed that the isolates collected in this study either represent generally nonpathogenic strains or that they represent strains pathogenic to plants other than tomato. Nevertheless, inoculation of the FOSC reference strain, Fo162, on various tomato cultivars and other plants, like melon, pepper, Arabidopsis and banana has never resulted in disease development Vu et al 2006;Martinuz et al 2015).…”
Section: Diversity Of Root Endophytesmentioning
confidence: 99%
“…Fungal root endophytes are a phylogenetically diverse group primarily occurring within the Ascomycota, although some belong to the Basidiomycota. Piriformospora indica (phyllum Basidiomycota) and particular isolates within Trichoderma and Fusarium species (phylum Ascomycota) have been reported to enhance growth of various plant species and to induce resistance to pests like insects and nematodes (Daneshkhah et al 2013;Vu et al 2006). Some research has also revealed positive effects of dark septate endophytes (DSE) which comprise a group of asexual ascomycetes and are characterized by dark melanized septa on plant growth, yield and nutrient uptake (Andrade-Linares et al 2011;Jumpponen 2001).…”
Section: Introductionmentioning
confidence: 99%
“…8) Endophytes protect hosts to some extent against pathogens, [9][10][11] reflecting the production of secondary metabolites, [12][13][14][15][16][17] fungal parasitism, 18) or induction of systemic resistance. 19,20) Since recognizing medicinal plants as a repository of fungal endophytes with novel metabolites of pharmaceutical importance, [21][22][23][24] many studies of species of species composition, relative abundance and associations of endophytic fungi have focused on medicinal plants. [25][26][27] Alpine medicinal plants is challenged by low temperature, a shorter vegetation period, more snow, and harsher conditions by the rising number of weather-related extreme events.…”
mentioning
confidence: 99%
“…It should be distinguished between a direct or indirect interaction of the organisms. Split root experiments were realized according to studies on interactions among soil-borne organisms and induced resistance (Hallmann and Berg, 2006;Khan, 1993;Vu et al, 2006,).…”
Section: Rhizoctonia Crown and Root Rot (Rcrr) Caused Bymentioning
confidence: 99%